Estimation of mechanical properties of Mg-5Zn-0.5Al-xSn alloy based on virtual crystal approximation. Issue 10 (October 2022) - Zhang, Yu; Wang, Bo; Wei, Shicheng; Wang, Yujiang; Li, Linwei
Abstract: First-principles calculations of multi-component alloys have been studied in detail. Herein, the first-principles calculations of Mg-5Zn-0.5Al-xSn alloys were performed by using the virtual crystal approximation (VCA) method. By calculating the lattice constants and elastic constants of the Mg-5Zn-0.5Al-xSn doping models, it was found that the mechanical properties and micro-hardness were related with the content of Sn. With the increase of Sn content, and the best ductility and the smallest micro-hardness were achieved at Sn = 2 wt.%. To verify the calculation results, the Mg-5Zn-0.5Al-xSn alloys were prepared and micro-hardness and tensile tests were conducted. The experiments demonstrate that the trends in mechanical properties obtained from the experiments are in agreement with the VCA computational results. These findings indicate that the VCA method has guiding significance in industries for rapid screening of high-performance Mg alloys. Abstract : First-principles calculations; Virtual crystal approximation; Multi-component Mg alloys; Mechanical properties